FEATURES OF THE CLINICAL COURSE OF ACUTE RESPIRATORY INFECTIONS AT PRESCHOOLERS WITH OVERWEIGHT - T. A. Sirotchenko; A. V. Mirgorodskaya; G. G. Bondarenko; O. A. Bugaenko (Union of pediatricians of Russia, 2019)
.